A Trainer's Guide to the Creative Curriculum for Family Child Care - Dodge, Diane Trister; Colker, Laura J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This trainer's guide presents two approaches to working with providers who are implementing The Creative Curriculum for Family Child Care. The first approach involves periodic workshops and sharing sessions for providers. The second approach involves individualized support offered by the trainer in each provider's home. In Chapter I, Planning Effective Training Sessions, a review of knowledge about adult learners provides a basis for planning training. The chapter offers practical suggestions on logistics, training techniques, communication with providers, and assessment of training. Chapter II, Workshops on the Creative Curriculum, includes detailed workshop outlines for each major activity area in the curriculum. Chapters III and IV focus on the process of working with providers in their homes, giving particular attention to preparation of the environment and implementation of activities. These chapters explain what should happen in family child care homes where the creative curriculum is used and indicate the importance of these happenings. These chapters also deal with typical problems that providers experience and strategies for helping providers address such problems. An appendix lists resources that supplement the curriculum and professional organizations providers can join. (RH)
Availability: Teaching Strategies, Inc., P.O. Box 42243, Washington, DC 20015 ($22.95; discount on orders over 10 copies).
Sponsoring Agency: Administration for Children, Youth, and Families (DHHS), Washington, DC. Head Start Bureau.
ERIC Note: For the Curriculum, see PS 019 441.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Caregivers; Curriculum; Early Childhood Education; Educational Environment; Family Day Care; Guidelines; Learning Activities; Planning; Resource Materials; Teaching Guides; Teaching Methods; Training; Workshops; Creative Curriculum for Family Child Care -- Curriculum Implementation; Guides, Classroom -- Teacher